Desenvolvimento gramatical e capacidades precoces de processamento linguístico: a aquisição dos princípios A e B da teoria de ligação em Português Brasileiro (PB) - Marinho, Nathálya Fernandes Inácio (2018)
Language acquisition studies have evolved significantly, seeing the concern to study how the child acquires a language in such a short time and in a natural way. Research in this area is based on different aspects of the acquisition, but in the present study, we highlight the development of the child's linguistic ability to recognize co-referential relationships between the elements of a sentence. Within this theme, one of the most significant is the study of the referential relations regulated by the binding principles that are defined by the Binding Theory (CHOMSKY, 1981). This research follows the line of several previous ones, such as the one by Chien and Wexler (1990) on the interpretation of Principles A and B by children of 5 years old, English native speaking, which is considered the inaugural work in this theme. Other works that were also focused on determining the level of domain of application of the binding principles in correctness identification tasks of the referents of reflexive pronouns and anaphora, such as the studies of Padilla (1990), Avrutin & Wexler (1992), McKee (1992), Sigurjonsdóttir & Hyams (1992) Grodzinsky & Kave (1993) and Jakubowicz (1994), besides the works of Grolla (2010, 2011, 2012) with data from Brazilian Portuguese (PB). The two experiments reported here have the main purpose to approach these questions related to the acquisition of binding principles. Using the experimental technique of cross-modal picture selection task (McAFEE et al., 1993) we aim to investigate if the processing of the anaphoric relations ruled by the binding principles A and B impose differences, implying that the processing time of the anaphoric relation of the principle as an indication of the procedural cost. Furthermore, we describe the acquisition process by comparing the performance of speakers in 3 distinct age groups (3-5 years, 6-8 years, adults), in order to establish possible differences between these groups in the domain of the binding principles. Finally, through the analysis of the correctness rate of the participants in the tasks of recognition of the correct referent of reflexive pronouns and anaphora, we intend to provide more empirical evidence on the question of the role of principles in the interpretation of the anaphora. With regard to the results of Experiment 1, we affirm that the binding principles impose different procedural demands, which are reflected in the average times in which the anaphoric relations are processed, since the sentences in which there was the action of the Principle A were processed more slowly than the sentences in which there was the action of Principle B, besides pointing to differences in the processing cost among the studied age groups, going exactly in the way of what was expected. The results of Experiment 2 were similar to the first one confirming the hypothesis that age is a factor that influences the processing and that in PB the delay in the processing of the sentences with principle B is not confirmed. In relation to ele mesmo/ela mesma, children processed more slowly the sentences in which principle A acted, and this fact can be justified by the little use of this anaphora in PB.